Propriedades mecânicas dos naphthylenes - Dantas, Dênis Giovanni de Medeiros (2023)
Since its discovery and synthesis in 2004, graphene has been gaining increasing attention in the scientific community due to its broad applicability in various technological fields. Over the years, new carbon-based two-dimensional materials have been discovered, and one of the most recent ones, discovered in 2019, is the Naphthylene. This material consists of a family of three structures known as alpha, beta, and gamma. In this study, we investigate the mechanical properties of these materials through uniaxial deformation using two distinct methods: (i) classical molecular dynamics (MD) employing the LAMMPS (Large-scale Atomic Molecular Massively Parallel Simulator) program in conjunction with the Tersoff three-body interatomic potential; and (ii) quantum simulations based on density functional theory (DFT) using the SIESTA code. We compare the results obtained from both methods and analyze how vacancy defects in different carbons affect the mechanical properties of naphthylenes. We found that the results obtained with MD for naphthylene-α show good agreement with the quantum method. The naphthylene-β structure exhibited the highest elastic constant and the least susceptibility to failure, comparable to graphene. Naphthylene-γ was found to be the least resistant to fractures. None of the studied materials are isotropic; they exhibit different elastic constants and distinct non-uniform stress distributions when deformed in different directions.